PENGGUNAAN METODE PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN MATEMATIKA KELAS VIII DI SMPN 1 KETUNGAU HULU - YOPPIYANA, AGNES (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
The low student mathematics learning outcomes are caused by less innovative learning media and a lack of connection between learning material and real life contexts. Based on this, research was conducted which aimed to improve the mathematics learning outcomes of class VIII students after implementing the problem based learning model. This research is classroom action research carried out in two cycles. Each cycle has four stages, namely: planning, implementation, observation and reflection. The subjects of this research were 21 class VIIIa students, consisting of 11 men and 10 women. The object of the research is students' mathematics learning outcomes, data analyzed using descriptive statistics. The research results show that the problem basic learning model can improve mathematics learning outcomes for class VIIIa. This is known from the pre-cycle student learning results with an average result of 71.09 and learning completeness of 30% in the low category. In cycle one, the average score was 75.20 and learning completeness was 54%, which was in the sufficient category. The research continued in cycle II and obtained an average score of 82.11 and learning completeness of 95% which was in the high category and had met the success indicator criteria. So, it can be concluded that the application of the problem based learning model can improve student learning outcomes. ABSTRAKRendahnya hasil belajar matematika siswa disebabkan oleh media pembelajaran yang kurang inovatif dan kurangnya keterkaitan antara materi pembelajaran dan kontek kehidupan nyata. Berdasarkan hal tersebut, maka diadakan penelitian yang bertujuan untuk meningkatkan hasil belajar matematika siswa kelas VIII setelah penerapan model pembelajaran problem based learning. Penelitian ini merupakan penelitian tindakan kelas yang dilaksanakan dalam dua siklus. Setiap siklus memiliki empat tahapan yaitu : perencanaan, pelaksanaan, observasi dan repleksi. Subjek penelitian ini adalah siswa kelas VIIIa yang berjumlah 21 orang, terdiri atas 11 laki – laki dan 10 perempuan. Objek penelitian adalah hasil belajar matematika siswa data dianalisis menggunakan statistic deskripsiptif. Hasil penelitian menunjukan bahwa model pembelajaran problem basic learning dapat meningkatkan hasil belajar matematika kelas VIIIa. Hal ini diketahui dari hasil belajar siswa pra siklus dengan hasil rata rata 71,09 dan ketuntasan belajar 30% beada pada kategori rendah. Pada siklus satu dengan nilai rata rata 75,20 dan ketuntasan belajar 54 % yang berada pada kategori cukup. Penelitian dilanjutkan pada siklus II dan memperoleh nilai rata rata 82,11 serta ketuntasan belajar 95 % yang berada pada kategori tinggi dan sudah memenuhi kriteria indicator keberhasilan. Jadi, dapat disimpulkan bahwa penerapan model pembelajaran problem based learning dapat meningkatkan hasil belajar siswa.